Relation of childhood gastrointestinal disorders to autism: nested case-control study using data from the UK General Practice Research Database - Black, Corri (BMJ, 2002)
OBJECTIVES: To assess whether children with autism are more likely to have a history of gastrointestinal disorders than children without autism. DESIGN: Nested case-control study. SETTING: UK General Practice Research Database. SUBJECTS: Children born after 1 January 1988 and registered with the General Practice Research Database within 6 months of birth. OUTCOME MEASURES: Chronic inflammation of the gastrointestinal tract, coeliac disease, food intolerance, and recurrent gastrointestinal symptoms recorded by the general practitioner. RESULTS: 9 of 96 (9%) children with a diagnosis of autism (cases) and 41 of 449 (9%) children without autism (matched controls) had a history of gastrointestinal disorders before the index date (the date of first recorded diagnosis of autism in the cases and the same date for controls). The estimated odds ratio for a history of gastrointestinal disorders among children with autism compared with children without autism was 1.0 (95% confidence interval 0.5 to 2.2). CONCLUSIONS: No evidence was found that children with autism were more likely than children without autism to have had defined gastrointestinal disorders at any time before their diagnosis of autism.